Verbal communication and motor control in a system-theoretical perspective - Petryński, Wacław; Szyndera, Mirosław (Akademia Wychowania Fizycznego w Poznaniu)
The authors outline the general bases of possible scientific development in motor control, and they argue that in this discipline it is theoretical conceptualization rather than empirical investigations, that is of crucial importance. More over, the bulk of motor control as a science remains an area hardly accessible to empirical researchers. The authors present three ways of anticipation: induction, abduction, and deduction. They propose taking abductive methodology and employing a systemic approach to theory development. Next, they present two important principles determining the motor behavior of human individuals: the “inverted-V principle” and the “descending firework principle”. The theoretical concepts make the “abductive part” of the paper, and then the authors take the “deductive way” and show how the described principles act in three typical daily life situations
Keywords: induction; abduction; deduction; motor control; system-theoretical approach